KONSTRUKSI HARMONI INTERNAL MELALUI STRATEGI KOMUNIKASI ORGANISASI (Studi Pada Humas Pemerintah Kota Batu) - sahertian, christiana; Elbaar, Stella (Jurnal Nomosleca, 2016)
Abstract The communication strategy is important in an organization because of the fact that the communication strategy issues arise in the process of organizing. Batu City Government Public Relations is the central point of information for people inside and outside government. The effectiveness of the organization lies in the effectiveness of communication, because to produce a common understanding between the sender and the receiver at all levels in the organization. The communication strategy within an organization's internal cohesion is seen as one of the factors determining the success or failure of an organization. To achieve internal Public Relations has a major role, especially the leadership role. This research uses descriptive qualitative method. Results of research conducted in Kota Batu Government Public Relations shows that systematically implementing communication strategies of organizations to achieve organizational goals with Stone City Government Public Relations, which can build up and build up a good internal harmony. But it needs to be realized in the form of written guidelines.DOI :Â https://doi.org/10.26905/nomosleca.v2i2.623